Topology control with coverage and lifetime optimization of wireless sensor networks with unequal energy distribution. (November 2017) - Xenakis, A.; Foukalas, F.; Stamoulis, G.; Katsavounidis, I.
Abstract: In this work, we use an unequal energy distribution algorithm, with which we succeed to extend network lifetime. In the sequel, we, we provide the best effort coverage by arranging the nodes using topology control principles. We formulate an optimization problem and define an objective function that incorporates both network coverage and lifetime that should be both maximized. Such a complex problem can be solved in polynomial time through Simulated Annealing (SA). An updated topology is evaluated in each convergence point and a near optimal node placement together with near optimal unequal energy allocation charge scheme is achieved. Results reveal that the proposed near optimal topology leads to greater coverage and lifetime as compared to several random deployments. We complete this work by providing a reliability study of the results, which is carried out by analysing the survival function of the derived statistical propertied of the proposed objective function.